Transcriptome and Volatilome Analysis During Growth of Brochothrix thermosphacta in Food: Role of Food Substrate and Strain Specificity for the Expression of Spoilage Functions - Illikoud, Nassima; Gohier, Rodérick; Werner, Dalal; Barrachina, Célia; Roche, David; Jaffrès, Emmanuel; Zagorec, Monique (Frontiers in Microbiology, 2019)
Brochothrix thermosphacta is one of the main spoilers in food, responsible for meat and seafood spoilage through the production of malodorous volatile organic compounds. The molecules produced by this bacterium depend on the substrate (meat or seafood) and the storage conditions such as gas mixtures used in the packaging. It seems also that the spoilage potential is strain dependent as production of diacetyl and acetoin, two molecules responsible for seafood spoilage, varies with strains. Therefore this suggests the involvement of different metabolic functions depending on both food substrate and strain capacities. In this study we selected two strains with different abilities to produce diacetyl and acetoin and compared their behavior after grown in beef or cooked peeled shrimp juices. We determined the genes up-regulated by both strains depending on the growth substrate and those that were specifically up-regulated in only one strain. The genes up-regulated by both strains in meat or in shrimp juice revealed the importance of the substrate for inducing specific metabolic pathways. The examination of genes that were specifically up-regulated in only one of the two strains revealed strain specificities that could be involved in strain fitness associated to specific substrates and also strain specific regulations of metabolic pathways putatively leading to different levels of spoilage molecule production. This shows the spoilage potential of B. thermosphacta depends on nutrients provided by food substrate and on the fitness and metabolic activity potential that each strain possesses.